Long-term organic selenium supplementation overcomes the trade-off between immune and antioxidant systems in pacu (Piaractus mesopotamicus) - Takahashi, Leonardo Susumu [UNESP] (2017)
Selenium (Se) is an essential nutrient for antioxidant defenses in fish because of its role in preventing immunosuppression caused by oxidative stress. In this study it was demonstrated the relation between the oxidative stress and immune status after a long Se supplementation period, as a result of the evaluation of immunological, hematological and antioxidant responses, as well as growth performance of pacu fed diets supplemented with different concentrations of organic selenium (0, 0.3, 0.6, 0.9, and 1.8 mg Se-yeast/kg, but the final analyzed selenium concentrations were 0.72, 0.94, 1.15, 1.57 and 2.51 mg/kg, respectively) for 65 days. Dietary Se supplementation at 1.15 mg Se-yeast/kg (analyzed value) restored the production of antioxidant enzymes (glutathione peroxidase (GPx) and glutathione S-transferase (GST)), and consequently allowed the increased of some immunological parameters (leukocyte respiratory burst activity and lysozyme activity), hematological parameters (red blood cell count (RBC), hematocrit (HTC), mean corpuscular volume (MCV), and white blood cell count (WBC)). Se supplementation in pacu diets at 1.15 mg Se-yeast/kg for 65 days improved immune response and antioxidant defenses, suggesting that oxidative stress impairs immune system response to prevent excessive reactive oxygen species in cells and indicating the occurrence of a physiological trade-off between immune and antioxidant systems. Higher Se levels, such as 1.57 mg Se-yeast/kg increased the leukocyte respiratory burst activity, the WBC and thrombocyte counts, the RBC and HTC, and the GST and GPx enzymes. However, 2.51 mg Se-yeast/kg decreased the lysozyme levels, the WBC and thrombocyte counts, the RBC, HTC and MCV, and the GST and GPx enzymes. Those findings are important to future studies because showed the negative effect of oxidative stress on immunity, and may help to prevent any inhibition of the expected immune response after immunomodulators administration and vaccination. Also it was possible to meet the dietary selenium requirement of pacu, that was estimated to be 1.56 mg/kg.